Homotopy Perturbation Method for Solving Reaction-Diffusion Equations - Yu-Xi Wang (Mathematical Problems in Engineering, 2008)
The homotopy perturbation method is applied to solve reaction-diffusion equations. In this method, the trial function (initial solution) is chosen with some unknown parameters, which are identified using the method of weighted residuals. Some examples are given. The obtained results are compared with the exact solutions, revealing that this method is very efficient and the obtained solutions are of high accuracy.